2021
DOI: 10.1186/s12935-021-02046-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ARNTL2 is associated with poor survival and immune infiltration in clear cell renal cell carcinoma

Abstract: Background Aryl hydrocarbon receptor nuclear translocator like 2 (ARNTL2) is a member of the PAS superfamily. Previous studies explored the carcinogenic roles of transcription factor ARNTL2 in human malignancies. However, its roles in ccRCC have not been elucidated. This study sought to explore the roles of ARNTL2 in ccRCC and determine its correlations with tumor immunity. Methods The expression of ARNTL2 was analyzed using the GEO, TCGA and GTEx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Moreover, a recent study demonstrated that high expression of ARNTL2 was associated with infiltration of CD8 + T cell, CD4 + memory T cell, Myeloid dendritic cell, macrophage and CD4 + Th2 T cell in clear cell renal cell carcinoma (ccRCC). 43 Thus, the results of the present study and others demonstrated that ARNTL2 may functionally link with immune responses in the tumor microenvironment and represent a potential indicator for immune cell infiltration.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, a recent study demonstrated that high expression of ARNTL2 was associated with infiltration of CD8 + T cell, CD4 + memory T cell, Myeloid dendritic cell, macrophage and CD4 + Th2 T cell in clear cell renal cell carcinoma (ccRCC). 43 Thus, the results of the present study and others demonstrated that ARNTL2 may functionally link with immune responses in the tumor microenvironment and represent a potential indicator for immune cell infiltration.…”
Section: Discussionsupporting
confidence: 74%
“…As an important biorhythm-related gene, ARNTL has been reported to play an oncogenic role in many human cancers. For example, Prior studies found that upregulation of ARNTL2 is associated with poor survival and immune in ltration in clear cell renal cell carcinoma 15 . Mazzoccoli et al reported that ARNTL2 is upregulated in colorectal cancer and is related to tumor invasiveness and aggressiveness 16 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Previous studies have reported that the prognosis of KIRC is closely related to immune-infiltrating macrophages, CD4+ T cells, CD8+ T cells, and regulatory T cells. 9 , 10 The treatment outcome of LIHC is believed to be correlated with infiltrating macrophages, B cells, CD4+ T cells, neutrophils, and dendritic cells. 11 The immunoregulatory molecules PD1, PD-L1, PD-L2, and CTLA4 are believed to be involved in the malignant progression of KIRC, 9 and PD-1 and CTLA-4 are believed to be associated with a poor prognosis of LIHC.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 The treatment outcome of LIHC is believed to be correlated with infiltrating macrophages, B cells, CD4+ T cells, neutrophils, and dendritic cells. 11 The immunoregulatory molecules PD1, PD-L1, PD-L2, and CTLA4 are believed to be involved in the malignant progression of KIRC, 9 and PD-1 and CTLA-4 are believed to be associated with a poor prognosis of LIHC. 12 These findings suggest that tumour-infiltrating immune cells may be a promising therapeutic target for KIRC and LIHC.…”
Section: Introductionmentioning
confidence: 99%